CD4+ T Cells Modified by the Endoribonuclease MazF Are Safe and Can Persist in SHIV-infected Rhesus Macaques - Naoki Saito; Hideto Chono; Hiroaki Shibata; Naohide Ageyama; Yasuhiro Yasutomi; Junichi Mineno (Elsevier, 2014)
MazF, an endoribonuclease encoded by Escherichia coli, specifically cleaves the ACA (adenine-cytosine-adenine) sequence of single-stranded RNAs. Conditional expression of MazF under the control of the HIV-1 LTR promoter rendered CD4+ T cells resistant to HIV-1 replication without affecting cell growth. To investigate the safety, persistence and efficacy of MazF-modified CD4+ T cells in a nonhuman primate model in vivo, rhesus macaques were infected with a pathogenic simian/human immunodeficiency virus (SHIV) and transplanted with autologous MazF-modified CD4+ T cells. MazF-modified CD4+ T cells were clearly detected throughout the experimental period of more than 6 months. The CD4+ T cell count values increased in all four rhesus macaques. Moreover, the transplantation of the MazF-modified CD4+ T cells was not immunogenic, and did not elicit cellular or humoral immune responses. These data suggest that the autologous transplantation of MazF-modified CD4+ T cells in the presence of SHIV is effective, safe and not immunogenic, indicating that this is an attractive strategy for HIV-1 gene therapy.